Increasing Vocabulary Repertoire through the Use of Internet Applications in Teaching and Learning EFL Students - Khalid Nayef Salem (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2022)
This study aims at shedding the light on the main points that affect and enhance learning English through using internet disciplines such as websites and electronic applications especially word recognition part of learning English . Many programmes of learning English are applied through internet and through previous studies and surveys emphasized that learners get a high opportunities in learning English using and practicing internet communications or calls. Since many previous studies conclude that, there are difficulties in learning English in Iraqi schools, so learners needs can show us a practical and rapid path that can facilitate English teachers’ mission by using electronic technology. Moreover, another obvious problem of learning English is continuous using of mother tongue inside classrooms while most of the learning programmes encourage learners to practice English from the early and advanced stages.